ANALISIS PENGARUH KUALITAS PRODUK, KEPUASAN PELANGGAN DAN WORDS OF MOUTH TERHADAP MINAT BELI ULANG KONSUMEN (Studi Kasus Pada Produk Kerupuk Ikan Lele UKM Minasari Cikaria Pati, Jawa Tengah) - Pamenang, Wisnu; Soesanto, Harry (Master of Management Diponegoro University, 2016)
Minasari Cikaria products are crackers catfish product that is already known by people around the village of Sukoharjo, Pati regency. In the last 1 year Cikaria Minasari sales decreased, therefore conducted this study to determine how to influence the Repurchase Intention cracker products UKM Minasari Cikaria.This research analyzes the factors that influence repurchase intention with mediating variables Word Of Mouth. In this study developed a theoretical model to propose five hypotheses to be tested using Structural Equation Model (SEM) using AMOS 21.0 software. Respondents were used in this study are all people who have purchased and consumed Minasari Cikaria totaling 270 people.The results of data processing for the full model SEM has met Godnessof Fit as follows, Value Chi Square = 78, 447, df: 49, p: 5%; Probability = 0.005; GFI = 0.954; AGFI = 0.927; TLI = 0,990; CFI = 0.993; CMIN / DF = 1.601; RMSEA = 0.047. Thus it can be said that this model is feasible to use. The results of this study indicate that word of mouth can be improved with quality products and customer satisfaction. Furthermore, customer satisfaction and word of mouth will affect the high repurchase intention of Minasari Cikaria products.